An Ode to Interdisciplinary Research: On the Example of Qualitative Study with Certified Translators - Karpińska, Patrycja (Journal of Education Culture and Society, 2025)
Aim. The aim of this paper is to discuss selected interdisciplinary threads that emerged from a qualitative study with Polish certified translators of English. While the overarching aim of the study was to explore the social space(s) in which certified translators function, the inquiry revealed many other issues reaching beyond the original scope of the study. Methods. The material for the study was gathered through in-depth interviews with ten certified English translators. The framework for the study was offered by Bourdieusian field theory (Bourdieu, 2001), following the example of the literary field, and the concept of understanding interview (Kaufmann, 2001). Results. The results are categorised into five perspectives that can be taken in the study. The methodological section tackles the sampling issue and how sample development may be highly informative. The educational section presents translators’ reflections and needs related to their education. The linguistic section shows how cognitive linguistics may be used to deepen the interpretation of collected material. The communicative perspective focuses on how interviews allow for an in-depth contextualisation of communication-related difficulties. The sociological perspective discusses the results as interpreted with the field theory. Conclusions. Interdisciplinarity, though it is sometimes considered an overused concept, may still bring novel perspectives and lead to valuable findings. The discussed study with certified translators shows how respect for other disciplines and changing vantage points may result in surprising discoveries.